A randomised, double blind, placebo controlled, multicentre trial of combination therapy with methotrexate plus ciclosporin in patients with active psoriatic arthritis. Issue 6 (4th November 2004) - Fraser, A D; van Kuijk, A W R; Westhovens, R; Karim, Z; Wakefield, R; Gerards, A H; Landewé, R; Steinfeld, S D; Emery, P; Dijkmans, B A C; Veale, D J
Abstract : Objectives: To evaluate the safety and efficacy of adding ciclosporin A (CSA) to the treatment of patients with psoriatic arthritis (PsA) demonstrating an incomplete response to methotrexate (MTX) monotherapy. Methods: In a 12 month, randomised, double blind, placebo controlled trial at five centres in three countries, 72 patients with active PsA with an incomplete response to MTX were randomised to receive either CSA (n = 38) or placebo (n = 34). Patients underwent full clinical and radiological assessment and, in addition, high resolution ultrasound (HRUS) was performed at one centre. An intention to treat (last observation carried forward) analysis was employed. Results: Some significant improvements were noted at 12 months in both groups. However, in the active but not the placebo arm there were significant improvements in swollen joint count, mean (SD), from 11.7 (9.7) to 6.7 (6.5) (p<0.001) and C reactive protein, from 17.4 (14.5) to 12.7 (14.3) mg/l (p<0.05) as compared with baseline. The Psoriasis Area and Severity Index (PASI) score improved in the active group (2 (2.3) to 0.8 (1.3)) as compared with placebo (2.2 (2.7) to 1.9 (2.8)), p<0.001, and synovitis detected by HRUS (33 patients, 285 joints) was reduced by 33% in the active group compared with 6% in the placebo group (p<0.05). No improvement in Health Assessment Questionnaire or pain scores was detected. Conclusions: Synovitis detected by HRUS was significantly reduced. Combining CSA and MTX treatment in patients with active PsA, and a partial response to MTX, significantly improves the signs of inflammation but not pain or quality of life.